Кыдёкын - а инвис?: пиналъёслы повестьёс / Герман Ходырев - Ходырев Герман Алексеевич (Удмуртия, 2001)
Экземпляры: ХР (20180522) / Инвентарный номер: 38223 / Цена: 77 / Сис.шифр: С(Удм) / Авт.знак: Х 69 / ГРНТИ: 17.82.31 / ББК: С(Удм)